Neurodevelopmental Effects of Serotonin on the Brainstem Respiratory Network - Eugenin-Leon, J; Llona-Rodriguez, I; Bravo-Flores, K (Springer New York LLC, 2017)
Serotonin has multiple roles during development of the nervous system. Human pathologies, mouse genetic models, and pharmacological experiments have demonstrated a role of serotonin in the development of neural networks. Here we summarize evidence showing that serotonin is important for the brainstem respiratory network. The available data highlight the role of serotonin as a developmental signal that previously has not been specifically considered for the respiratory network. © Springer International Publishing AG 2017.